PREVENTION OF SPINAL DISORDERS IN CHILDRENI- IV GRADE - Dejаn Gojković; Zoran Milinković (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2012)
Problem physical activities children younger school-age children, with the basic tasks research is construction kinesitherapy adequate prevention and avoid postural disorders spinal column, optimal ontogenetic level morphological( anthropological) development.The main objective research is contents teaching physical education as well as and content that can be put in regular program teaching physical education with the basic task prevention potential and eliminate disorders spinal column, with auxiliary a harmonious biological development. The entities from which he was carried out sample size for this research is defined as population students male primary schools I- IV grade.The first and basic condition was that they are included in teaching physical education in the course of this research sample is taked 400 respondents.-according to the manner elections respondents sample was targeted selected.were taken I- IV grade elementary schools in Bijeljina, Teslic, Foca and Pale.